Epigenetic Regulation of S100A9 and S100A12 Expression in Monocyte-Macrophage System in Hyperglycemic Conditions - Mossel, Dieuwertje M.; Moganti, Kondaiah; Riabov, Vladimir; Weiss, Christel; Kopf, Stefan; Cordero, Julio; Dobreva, Gergana; Rots, Marianne G.; Klüter, Harald; Harmsen, Martin C.; Kzhyshkowska, Julia (Frontiers in Immunology, 2020)
The number of diabetic patients in Europe and world-wide is growing. Diabetes confers a two-fold higher risk for vascular disease. Lack of insulin production (T1D) or lack of insulin responsiveness (T2D) causes systemic metabolic changes such as hyperglycemia (HG) which contribute to the pathology of diabetes. Monocytes and macrophages are key innate immune cells that control inflammatory reactions associated with diabetic vascular complications. Inflammatory programming of macrophages is regulated and maintained by epigenetic mechanisms, in particular histone modifications. The aim of our study was to identify the epigenetic mechanisms involved in the hyperglycemia-mediated macrophage activation. Using Affymetrix microarray profiling and RT-qPCR we identified that hyperglycemia increased the expression of S100A9 and S100A12 in primary human macrophages. Expression of S100A12 was sustained after glucose levels were normalised. Glucose augmented the response of macrophages to TLR-ligands PA and LPS i.e. pro-inflammatory stimulation. The abundance of activating histone marks H3K4me1, H3K4me3 and general acetylation on histone 3 with the promoters of these genes was analysed by chromatin immunoprecipitation. Hyperglycemia increased acetylation of histones bound to the promoters of S100A9 and S100A12 in M1 macrophages. In contrast, hyperglycemia caused a reduction in total H3 which correlated with the increased expression of both S100 genes. The inhibition of histone methyltransferases SET7/9 and SMYD3 showed that these specifically regulated S100A12 expression. We conclude that hyperglycemia upregulates expression of S100A9, S100A12 via epigenetic regulation and induces an activating histone code on the respective gene promoters in M1 macrophages. Mechanistically, this regulation relies on action of histone methyltransferases SMYD3 and SET7/9. The results define an important role for epigenetic regulation in macrophage mediated inflammation in diabetic conditions.